FDM based flux distribution analysis method for electrical machines [Porównanie wyników analizy rozkładu strumienia magnetycznego w maszynach elektrycznych wykonanej eksperymentalnie i obliczeniowo] - (:unkn) unknown (My University, 2013)
The aim of this study is to compare the flux distributions obtained using the experimental method and calculated by FDM. For this purpose, first the design and manufacture of the test transformer which is to be used in the experimental study as well as the measuring coil which is to be used in measuring the prepared fluxes, and then the calculated flux values. Both proposed assessment methods can be used for in-service inspection of the structural integrity of ferromagnetic structures.
Keywords: Core-type voltage transformers; FDM; Leakage flux